Pengembangan Buku Cerita Bergambar Islami Berbasis Pendidikan Lingkungan Hidup untuk Pembelajaran Membaca di SD/MI - Nurul Hidayah; Rohmatillah Rohmatillah (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This research stems from the lack of variation in instructional media in teaching and learning activities, so it is necessary to develop a product in the form of a picture story book as a learning medium. The formulations of the problem are: (1) How is the development of learning media for Islamic picture book based on environmental education for reading learning in class III SD / MI, (2) Is it feasible to teach Islamic picture book learning media based on environmental education for learning to read in the classroom? III SD / MI, (3) How is the response of educators and students to the learning media of Islamic picture book based on environmental education for reading learning in class III SD / MI. This study aims to make students more interested and motivated in teaching and learning activities and understanding the importance of protecting the environment. This research is a research development or Research and Development with the ADDIE model which includes 5 steps, namely analysis, design, development, implementation evaluation. The product feasibility test was carried out by several validators, namely 2 media experts, 2 material experts, 2 linguists, 1 religious expert, 2 class III educators on grade III SD/MI students. The results showed that the learning media for Islamic picture book based on environmental education obtained an average value of the percentage of media experts who obtained a score of 80.25% with a very feasible category, material experts of 86.5% with a very decent category, linguists obtained a score 82.5% in the very feasible category, religious experts obtained a score of 87% in the very feasible category, the assessment of educators obtained an average percentage of 88.25% with the very feasible category and the response of students obtained an average percentage of 95.5% with a very decent category. This shows that the Islamic picture story book based on environmental education for reading learning in grade III SD / MI is very suitable for use as a learning medium.